Predictors of workplace deviant behaviour and the mediating role of job satisfaction among support staff in Malaysian local authorities - Alias, Mazni (2013)
This study examined the factors influencing workplace deviant behaviour and the mediating role of job satisfaction among support staff in the Malaysian Local Authorities. It is imperative for HRD practitioners to determine the factors predicting workplace deviant behaviour due to its implications on employee’s performance and organisation development. It has been reported that support staff workplace deviant behaviour has been at its highest percentage compared to other categories of employees in Malaysian public service organisations. Despite this high percentage, there is a lack of empirical evidence on the predictors of workplace deviant behaviour among support staff specifically in the Malaysian and Asian context. Researchers have also suggested that further research should focus on employing job satisfaction as a mediating variable in workplace deviant behaviour studies. This study used Mount, Judge and Ilies’s workplace deviant behaviour model, Social Exchange Theory, Affective Events Theory and General Strain Theory to explain the relationships between the individual-related factors (i.e., negative affectivity, conscientiousness, agreeableness, and emotional intelligence),organisational-related factors (i.e., organisational ethical climate, and organisational justice, perceived organisational support, trust in organisation), work-related factors (i.e., work stress and job autonomy), workplace deviant behaviour and job satisfaction as the mediating variable. This study adopted a cross sectional survey and employed a structured questionnaire in data collection. The study involved 429 respondents selected through two stages of cluster random sampling. Four clusters of population were randomly selected at the first stage, followed by the random selection of samples from the clusters at the second stage. Descriptive analysis and Structural Equation Modeling (SEM) using AMOS software in SPSS were used in the analysis. Results in the direct structural model revealed that negative affectivity, agreeableness, perceived organisational support, trust in organisation, and job autonomy influenced workplace deviant behaviour among respondents. However,conscientiousness, emotional intelligence, organisational ethical climate,organisational justice, and work stress did not influence workplace deviant behaviour. The full mediation model which is also the proposed model in this study also indicates a good model fit. Results revealed that job satisfaction fully mediates the relationship between perceived organisational support, and job autonomy on workplace deviant behaviour. In addition, the relationships between negative affectivity and agreeableness on workplace deviant behaviour were partially mediated by job satisfaction. This study provides a predictive framework explaining support staff engagement in workplace deviant behaviour. The findings of this study also would assist HRD researchers and practitioners in understanding the issues and strategies to reconcile the prevalence of workplace deviant behaviour.